Anesthetic considerations and perioperative management in chronic obstructive pulmonary disease: from pre-anesthetic evaluation to safe extubation - Velasco, Evelyn D. G.; Paucar, Carla D. S.; Narváez, Daniela L. B.; Cobos, María C. V.; Jaramillo, Saskya D. F.; Camacho, Anahy M. S. (International Journal of Research in Medical Sciences, 2026)
Chronic obstructive pulmonary disease represents one of the most prevalent respiratory comorbidities in surgical patients and constitutes a major independent risk factor for postoperative pulmonary complications, alveolar collapse, and ventilatory failure. Anesthetic management demands a comprehensive understanding of underlying pathophysiological alterations, such as air trapping, auto-PEEP, and ventilation-perfusion mismatch. Objectives of the study were to analyze current evidence regarding pre-anesthetic optimization, selection of anesthetic techniques, intraoperative ventilatory support, and strategies for safe extubation in patients with chronic obstructive pulmonary disease. A narrative literature review of scientific articles published in biomedical databases (PubMed, Scopus, Web of Science) was conducted, focusing on perioperative pulmonary risk stratification, protective mechanical ventilation, neuromuscular blockade, and regional analgesia techniques. Preoperative optimization through smoking cessation, optimized bronchodilator therapy, and respiratory physiotherapy significantly reduces the incidence of postoperative pulmonary complications. During general anesthesia, protective ventilation strategies featuring low tidal volumes (6-8 ml/kg of predicted body weight), prolonged expiratory time to mitigate dynamic hyperinflation, and judicious PEEP titration improve gas exchange. Regional anesthetic and analgesic techniques demonstrate a distinct advantage by preserving respiratory mechanics and decreasing opioid consumption. Complete, quantitative reversal of neuromuscular blockade represents a critical cornerstone in preventing extubation failure. Successful perioperative management of patients with chronic obstructive pulmonary disease requires a coordinated strategy spanning from precise risk stratification to structured ventilatory weaning. Strict application of intraoperative protective ventilation and optimized analgesic control significantly decrease morbidity, mortality, and hospital length of stay.